Analgesic activity of Adiantum flabellulatum (Dhaka University Journal of Biological Sciences, 2011)
Key words: Adiantum flabellulatum; Adiantaceae; Analgesic activityDOI: http://dx.doi.org/10.3329/dujbs.v20i1.8877Dhaka Univ. J. Biol. Sci. 20(1): 91-93, 2011 (January)